Coupling of thermal field-flow fractionation and FTIR spectroscopy for the fractionation and analysis of complex polymers - Radebe, Nonkululeko Winnie (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.